Maturation of small nucleolar RNAs: from production to function - Sarah F. Webster; Homa Ghalei (RNA Biology)
Small Nucleolar RNAs (snoRNAs) are an abundant group of non-coding RNAs with well-defined roles in ribosomal RNA processing, folding and chemical modification. Besides their classic roles in ribosome biogenesis, snoRNAs are also implicated in several other cellular activities including regulation of splicing, transcription, RNA editing, cellular trafficking, and miRNA-like functions. Mature snoRNAs must undergo a series of processing steps tightly regulated by transiently associating factors and coordinated with other cellular processes including transcription and splicing. In addition to their mature forms, snoRNAs can contribute to gene expression regulation through their derivatives and degradation products. Here, we review the current knowledge on mechanisms of snoRNA maturation, including the different pathways of processing, and the regulatory mechanisms that control snoRNA levels and complex assembly. We also discuss the significance of studying snoRNA maturation, highlight the gaps in the current knowledge and suggest directions for future research in this area.